Analysis of the Negative Effect of Online Games on the Learning Conditions of Students in Schools - Zainal, Zainal; Mulyani, Ridha; Japeri, Japeri; Burhanuddin, Burhanuddin; Sabri, Yuli (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
This research is motivated by online games which make students addicted to playing online games, student learning motivation decreases, and students become less disciplined with time, and students do not care about the environment around them only care about friends who are in the virtual world of online games. Based on statistical data and the strong influence of globalization, it shows that school-aged teenagers are addicted to online gameplay. Online games are one of the impacts that affect learning achievement. This study is intended to determine the behavior caused by online game addiction in students. Lack of interest in learning causes a decrease in student achievement so that which can create a lack of human resources due to low interest and motivation in learning. The purpose of this study is to find out how the impact of the influence of online games on student achievement. This type of research is qualitative research. Qualitative research used in this study was carried out using interviews or case studies. Data collection techniques by reading and recording important information contained in various journals related to research and conducting a review of the research object, namely and students who are affected by the influence of online games that are being carried out. Knowing how online games are among students, then this research can find out the causes of why students become addicted to playing online games and describe the impact and influence of online games on students' mentality.